2012
DOI: 10.1016/j.aop.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and nonlocality measures as indicators of quantum phase transitions in several critical systems

Abstract: We have investigated the quantum phase transitions in the ground states of several critical systems, including transverse field Ising and XY models as well as XY with multiple spin interactions, XXZ and the collective system Lipkin-Meshkov-Glick models, by using different quantumness measures, such as entanglement of formation, quantum discord, as well as its classical counterpart, measurement-induced disturbance and the Clauser-Horne-Shimony-Holt-Bell function. Measurement-induced disturbance is found to dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 73 publications
(148 reference statements)
1
43
0
Order By: Relevance
“…Evidently, it is demonstrated that the lack of any optimization procedure over the set of projective measurements in the definition of MID leads to a fact that MID can be non-full and even maximal on states exhibiting zero quantum correlations. Such many shortcomings make it a weak correlation measure for some states [21,[48][49][50]. Girolami et al [21] introduce an improved version of MID, i.e.…”
Section: Measurement-induced Disturbance and Its Improved Versionmentioning
confidence: 99%
“…Evidently, it is demonstrated that the lack of any optimization procedure over the set of projective measurements in the definition of MID leads to a fact that MID can be non-full and even maximal on states exhibiting zero quantum correlations. Such many shortcomings make it a weak correlation measure for some states [21,[48][49][50]. Girolami et al [21] introduce an improved version of MID, i.e.…”
Section: Measurement-induced Disturbance and Its Improved Versionmentioning
confidence: 99%
“…Indeed, different correlations may be associated with resources for distinct tasks. As for entanglement and discord, characterization of QPTs through Bell correlations between qubits through the Clauser-Horne-Shimony-Holt (CHSH) inequality has recently been addressed [14][15][16][17]. However, it is rather surprising that the CHSH inequality, when applied for any pair of qubits in critical spin latices, has been observed to be nonviolated in a number of different systems (see, e.g., Refs.…”
Section: P-1mentioning
confidence: 99%
“…Very recently, the CHSH inequality has been used as a tool to characterize QPTs [14][15][16][17]. In turn, it has successfully performed this task, indicating QPTs through nonanalyticities in the derivatives of the Bell correlations.…”
Section: Qpts Correlations and Chsh Inequality -mentioning
confidence: 99%
“…Recently, quantum discord in various spin models have been studied by a number of authors [46][47][48][49][50][51][52][53][54][55][56]. Particularly, the spin-1/2 model with Ising interactions between neighbors has attracted wide attention due to its clear physical picture.…”
Section: Introductionmentioning
confidence: 99%